2004
DOI: 10.1136/bmj.38267.664086.63
|View full text |Cite
|
Sign up to set email alerts
|

Prospective cohort study of cannabis use, predisposition for psychosis, and psychotic symptoms in young people

Abstract: Objective To investigate the relation between cannabis use and psychotic symptoms in individuals with above average predisposition for psychosis who first used cannabis during adolescence. Design Analysis of prospective data from a population based sample. Assessment of substance use, predisposition for psychosis, and psychotic symptoms was based on standardised personal interviews at baseline and at follow up four years later. Participants 2437 young people (aged 14 to 24 years) with and without predispositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

33
513
1
24

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 663 publications
(571 citation statements)
references
References 22 publications
(30 reference statements)
33
513
1
24
Order By: Relevance
“…In the current study, we did not replicate differences in THC sensitivity between patients and controls. However, rather than examining case-control differences, the design of the current study allowed for testing differential THC sensitivity at the level of psychometric psychosis liability, similar to earlier work (Henquet et al, 2005a;Verdoux et al, 2003). In agreement with these earlier studies, evidence for differential THC sensitivity was found, restricted to subjects with the Val/Val genotype.…”
Section: Thc Comt Val 158 Met Genotype and Cognitionsupporting
confidence: 74%
See 4 more Smart Citations
“…In the current study, we did not replicate differences in THC sensitivity between patients and controls. However, rather than examining case-control differences, the design of the current study allowed for testing differential THC sensitivity at the level of psychometric psychosis liability, similar to earlier work (Henquet et al, 2005a;Verdoux et al, 2003). In agreement with these earlier studies, evidence for differential THC sensitivity was found, restricted to subjects with the Val/Val genotype.…”
Section: Thc Comt Val 158 Met Genotype and Cognitionsupporting
confidence: 74%
“…Our diagnostic group was heterogeneous, including schizo-affective disorder and psychosis not otherwise specified apart from schizophrenia. The rationale for this relatively broad inclusion was that the effects of cannabis on psychotic symptoms and cognition, as well the interaction with prior psychometric psychosis liability, have been demonstrated both in populations of patients with a psychotic disorder and in nonpatient populations (D'Souza et al, 2005;Henquet et al, 2005a;Verdoux et al, 2003), suggesting relative nonspecificity across diagnostic groups and validating our approach of showing quantitative differences in sensitivity to cannabis between groups. Four relatives had diagnoses of affective disorder.…”
Section: Methodological Issuesmentioning
confidence: 98%
See 3 more Smart Citations